PENGARUH KOMPETENSI, KOMPENSASI, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SUMATERA JAYA AGRO LESTARI SILAUT - Henryanto Abaharis; Harzal Fauzi (LP2M Universitas Bina Bangsa, 2022)
The purpose of this study was to examine the effect of the variables Competence, Compensation and Job satisfaction on employee performance at PT. Sumatra Jaya Agro Lestari Silaut. Collecting data by distributing questionnaires to 63 respondents using a saturated sampling technique, where all members of the population are sampled, using multiple linear regression testing with the help of the SPSS application. The results of the study show that competence has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance